(untitled) (Acta Scientiarum. Agronomy, 2026)
Cadmium (Cd) and lead (Pb) contamination in agricultural and urban soils poses significant environmental and human health risks, especially in areas impacted by metallurgical waste. In this study, the efficacy of four biochars produced from rice straw (RSB), sugarcane bagasse (SBB), sewage sludge (SSB), and filter cake (FCB), in immobilizing Cd and Pb and improving soil chemical properties, was assessed. An incubation experiment was conducted using contaminated soil from Santo Amaro, Brazil, a site historically affected by lead smelting. Biochars were applied at 10% (w/w), and their effects on soil pH, nutrient availability, organic matter (SOM), and metal fractionation were evaluated. Compared with the control treatment, the SBB and FCB treatments significantly reduced the availability of Cd ( 30%) and Pb ( 20%). These biochars also increased phosphorus (P) availability and increased the SOM content. Sequential extraction indicated a shift of Cd and Pb from labile to more stable forms, particularly the reducible and residual fractions, suggesting improved long-term immobilization. The superior performance of SBB and FCB was attributed to their higher SOM and P contents, as well as functional groups that promote metal complexation. Overall, the findings demonstrate the potential of nutrient-rich, waste-derived biochars as a sustainable and cost-effective solution for the remediation of heavy metal-contaminated soils. The results highlight the importance of selecting biochars based on feedstock characteristics and underscore the need for field-based studies to evaluate their long-term stability and the effects on metal uptake by plants.